1999
DOI: 10.1016/s1074-7613(00)80021-7
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Invariant Chain Degradation and Antigen Presentation and Diminished Collagen-Induced Arthritis in Cathepsin S Null Mice

Abstract: Cathepsins have been implicated in the degradation of proteins destined for the MHC class II processing pathway and in the proteolytic removal of invariant chain (Ii), a critical regulator of MHC class II function. Mice lacking the lysosomal cysteine proteinase cathepsin S (catS) demonstrated a profound inhibition of Ii degradation in professional APC in vivo. A marked variation in the generation of MHC class II-bound Ii fragments and presentation of exogenous proteins was observed between B cells, dendritic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
348
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(367 citation statements)
references
References 44 publications
19
348
0
Order By: Relevance
“…It is involved in both the intracellular breakdown of li [9] and proteolytic processing of different antigens including myelin basic protein, a potential autoantigen implicated in the pathogenesis of MS [33]. CatS activity is required for induction of the MHC II-mediated collagen-induced arthritis [34]. Likewise, pharmacological inhibition of CatS suppresses autoimmunity in thyroiditis and pulmonal hypersensitivity [26].…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in both the intracellular breakdown of li [9] and proteolytic processing of different antigens including myelin basic protein, a potential autoantigen implicated in the pathogenesis of MS [33]. CatS activity is required for induction of the MHC II-mediated collagen-induced arthritis [34]. Likewise, pharmacological inhibition of CatS suppresses autoimmunity in thyroiditis and pulmonal hypersensitivity [26].…”
Section: Discussionmentioning
confidence: 99%
“…Processing of Ii appears to be based on redundant protease activities (Costantino et al 2008) with the exception of the cleavage of the p10 intermediate degradation product into CLIP. This requires cathepsin S (Riese et al 1996;Driessen et al 1999;Nakagawa et al 1999;Shi et al 1999) or cathepsins L and F (Nakagawa et al 1998;Shi et al 2000), depending on the cell type. Degradation of the remaining transmembrane fragment requires the intramembrane endopeptidase SPPL2A (Beisner et al 2013;Bergmann et al 2013;Schneppenheim et al 2013).…”
Section: Biosynthesis Of Mhciimentioning
confidence: 99%
“…An important role in antigen presentation has been identified for cathepsin S, which is involved in both the processing of endocytosed proteins to peptides suitable for presentation and the cleavage of the invariant chain to CLIP during MHC class II maturation (Riese et al, 1996;Shi et al, 1999;Villadangos et al, 1999). Studies of cathepsin S knockout mice revealed a decrease in their susceptibility to collagen-induced arthritis and impaired invariant chain processing in both dendritic cells and B cells (Nakagawa, Brissette et al, 1999). This suggests that antigen presentation, mediated by cathepsin S in dendritic cells and B cells is an important driving factor in the maintenance of inflammatory arthritis.…”
Section: Synovium: Inflammation Hyperplasia Pannus Formation and Prmentioning
confidence: 99%